Association between gestational visit‐to‐visit blood pressure variability and adverse neonatal outcomes. Issue 6 (14th May 2022) - Gu, Yingjie; Shi, Haofan; Zeng, Weijian; Zheng, Yulong; Yang, Mengnan; Sun, Mengru; Shi, Hong; Gu, Wei
Abstract: The authors aimed to explore the association between visit‐to‐visit blood pressure variability (BPV) in pregnant women and adverse neonatal outcomes. The study included 52 891 pregnant women. BPV was calculated as standard deviation (SD) and coefficient of variation (CV) of systolic blood pressure (SBP) or diastolic blood pressure (DBP). All participants were divided into four groups by the quartiles of BPV. When comparing the highest quartiles to the lowest quartiles of DBP SD in all participants, the fully adjusted ORs were 1.19 (95% CI 1.11–1.27, p for trend < .001) for fetal distress, 1.32 (95% CI 1.14–1.54, p for trend < .001) for small for gestational age, 1.32 (95% CI 1.06–1.63, p for trend = .003) for 1‐min Apgar score ≤ 7. When comparing the highest quartiles to the lowest quartiles of DBP CV, ORs were 1.22 (95% CI 1.14–1.30, p for trend < .001) for fetal distress, 1.38 (95% CI 1.17–1.61, p for trend < .001) for small for gestational age, 1.43 (95% CI 1.14–1.79, p for trend < .001) for 1‐min Apgar score ≤ 7. ORs for preterm birth and 5‐min Apgar score ≤ 7 were not statistically significant. However, in participants with gestational hypertension or preeclampsia, ORs for preterm birth were 2.80 (95% CI 1.99–3.94, p for trend < .001) in DBP SD and 3.25 (95% CI 2.24–4.72, p for trend < .001) in DBP CV when extreme quartiles were compared. In conclusion, higher visit‐to‐visit BPV was associated with adverse neonatal outcomes.